Permasalahan Mendasar Petugas Pemasyarakatan Dan Pencarian Akan Strategi Untuk Mengatasinya - Yunarsih, Rahma; Wibowo, Padmono (Jurnal Ilmiah Wahana Pendidikan, 2024)
Correctional officers have various types of obligations and responsibilities that are directly related to the course of social life in society. This is due to the role of the Correctional Officer which actually covers the management and development of humans who are marginalized or become enemies of the community due to mistakes or violations committed by them in the past. Correctional officers are tasked with providing guidance, supervision, and special counseling to those referred to as Correctional Inmates, it aims to prepare people who are serving the sentence to eventually be accepted again in the community. However, in fact there are still various mistakes or acts of unprofessional behavior carried out by a Correctional Officer, this is what then gave birth to a special search for strategies that can be determined to solve this very serious problem.